PEMBERDAYAAN DAN KEGIATAN PETANI MULTIKOMODITI DI PEDESAAN PROPINSI MALUKU: SUATU KAJIAN EKONOMI RUMAHTANGGA - HEATUBUN, ADOLF B.; SINAGA, BONAR M. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 1 Februari 2003, 2012)
This study aim to evaluate succession implementing the multicommodity farmers empowering program and to analysis, the impact of external factors change toward farmer’s decision. The farmer’s activity analyzed with simultaneous econometrics equation approach in the household economic model. Result of the study namely implementing of the empowering program only success technically, but not success increase the farmer’s welfare. Utilize and allocation of the labor, agricultural product and farmers disposible income have increased caused by increase of the commodity prices, wages and non agricultural income. The farmers should increase the activity motivation and to utilize the effort opportunity available. Program owner need to improvement the performance in implemented theirs program, in order always orientation to autonomy the farmers.
Keywords: Household Economic, Farmers Multicommodity, Empowering, Econometrics, Simulation